Analisis Penggunaan Media Pembelajaran Dalam Mengenalkan Kearifan Lokal Jawa Barat Pada Anak Usia Dini - Aisyah, Siti; Sianturi , Risbon; Rahman, Taopik (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
Local wisdom is an important part of culture that must be preserved and introduced to the younger generation, including young children. This research aims to identify the use of learning media in introducing West Java local wisdom to children aged 5-6 years at Al-Qolam Kindergarten. The research method used is qualitative with a descriptive approach. The research data sources consisted of teachers and group B children at Al-Qolam Kindergarten. Data collection techniques include observation, interviews and documentation. Data analysis is carried out by describing the data that has been collected. The results of the research show that in Al-Qolam Kindergarten learning media has been used in every lesson, but there is no special media designed to introduce West Java local wisdom to children aged 5-6 years.